Răspuns :
a) x + 3y - 3z = x + 2y + y - 3z = 17 + 4 = 21
b) 2x + 5y - 3z = 2(x + 2y) + (y - 3z) = 2 * 17 + 4 = 34 + 4 = 38
c) (3x + 6y) + (2y - 6z) = 3(x + 2y) + 2(y - 3z) = 3 * 17 + 2 * 4 = 51 + 8 = 59
d) (2x + 4y) * (x + 4y - 6z) = 2(x + 2y) * [(x + 2y) + 2(y - 3z)] =
2 * 17 * [17 + 2 * 4] =
34 * [17 + 8] =
34 * 25 =
850
b) 2x + 5y - 3z = 2(x + 2y) + (y - 3z) = 2 * 17 + 4 = 34 + 4 = 38
c) (3x + 6y) + (2y - 6z) = 3(x + 2y) + 2(y - 3z) = 3 * 17 + 2 * 4 = 51 + 8 = 59
d) (2x + 4y) * (x + 4y - 6z) = 2(x + 2y) * [(x + 2y) + 2(y - 3z)] =
2 * 17 * [17 + 2 * 4] =
34 * [17 + 8] =
34 * 25 =
850
---------------------------------------------------------------------------------------------------